THE IMPORTANCE OF BANK’S REPUTATION IN THE SELECTION OF BANKING PRODUCTS IN THE OPINION OF MIDDLE POMERANIAN FARMERS - Anna Rosa (Journal of Agribusiness and Rural Development, 2016)
Farmers, when choosing a bank whose services they want to use, are guided by various factors. The purpose of the research conducted was to select the most essential factors that determine the choice of a bank and an identification of connections between opinions on a bank (its reputation) and the selected features that characterize farmers from the Middle Pomeranian region. The primary data obtained in the course of the empirical field research conducted and a multidimensional correspondence analysis were used in the realization of the objective accepted. The following constituted the set of operands: the status and acreage of the farm, the type and the value of production, sex, age and education of the person in charge of the farm. As is evident from the research conducted, the opinion on a bank (its reputation) was the most essential determinant indicated in the selection of banks by farmers. The analysis demonstrated among others that those farmers polled who think that the opinion on the bank constitutes an important cause in the selection of banking products and services are in aged below 45, they possess secondary agricultural education and run farms with plant and animal production.